FORMULASI SABUN CAIR ANTISEPTIK SARI AIR KULIT BUAH PISANG AMBON (MUSA PARADISIACA VAR SEPIENTUM L.) DAN UJI AKTIVITAS ANTIBAKTERI TERHADAP STAPHYLOCOCCUS AUREUS DAN ESCHERICHIA COLI - Ramadani, Muhammad; Gunawan, Muhammad; Fitriani, Enny; Kusumastuti, Melati Yulia (Universitas Imelda Medan, 2024)
Cleanliness of the skin, hands and body is a state of being free of dirt, dust and microorganisms that can cause infection. The existence of these microorganisms can be overcome by using soap containing chemical compounds that have antibacterial activity. In the market there are many circulating antiseptic soaps containing synthetic antibacterials, but they often cause side effects, so it is necessary to make soaps containing natural antibacterials, for example, Ambon banana peel contains polyphenolic compounds and saponins have antibacterial activity. The study conducted a phytochemical screening of Ambon banana peels, made liquid soap containing water extract of Ambon banana peels as a cleanser and antibacterial and carried out antibacterial activity tests. Research stages: phytochemical screening of Ambon banana peel and water extract, liquid soap formulation containing 10%, 20% and 30% Ambon banana peel water extract (SKPA), evaluation of liquid soap including: stability, foam height, pH, irritation and preference test . Antibacterial activity test against Staphylococcus aureus, Escherichia coli and bacteria from volunteer hand washing water specimens. The results showed that the water extract from Ambon banana peel contains alkaloids, flavonoids, tannins, saponins, steroids/triterpenoids, and glycosides, which can be formulated into liquid soap (SKPA) fulfilling the physical quality requirements. SKPA 30% liquid soap is the best because it is very liked by researchers, has strong antibacterial activity, diameter of inhibition against Staphylococcus aureus (17.23 ± 0.66) mm, and Escherichia coli (15.83 ± 0.66) mm. The total plate number for volunteer hand washing specimens, 10% SKPA resulted in a reduction of bacterial colonies of 49.78%, 30% SKPA obtained the greatest reduction in bacteria, namely 82.79, almost the same as Dettol liquid soap. What is circulating in the market is 83.02%.